Ruminant gut microbiota: importance, development, and alternative therapeutics for dysbiosis - Albakri, Nahlah; Amasha, Reda; Aly, Magda M. (Journal of Contemporary Medical Sciences, 2023)
The microbiome is a population of microbes that colonized in mammalian gut. During the first few years of life, the gut microbiome undergoes alteration and is very diverse in adulthood, depends upon various of circumstances. Gut microbes, particularly gut flora in ruminants, are receiving more and more attention. Intestinal microbes, particularly ruminant microorganisms, have attracted an increasing amount of attention as high-throughput sequencing technology has improved and costs have decreased, whether in the fundamental research or application fields. The ruminant microbiome changes in conjunction with its host and it is influenced by inter-microbial interactions, environmental exposures, and host properties. However, any organism's core functional microbiome is much more conventional. Unfortunately, the fragile growth ratio of the microbial culture is susceptible to incursions under illness circumstances, which may affect the abundance of various microbial species, resulting to dysbiosis. As a result, the purpose of this review is to provide a broad summary of the relevance of ruminant gut microorganisms, as well as to investigate variables that influence the microbiota and alternative therapeutics such as probiotics, prebiotics, fecal transplantation, and rumen transfiguration, all of which have been shown to be effective in addressing dysbiosis.